Drosophila eyes absent is a Novel mRNA Target of the Tristetraprolin (TTP) Protein DTIS11 - Yeh, Po-An (Ivyspring International Publisher, 2012)
The Tristetraprolin (TTP) protein family includes four mammalian members (TTP, TIS11b, TIS11d, and ZFP36L3), but only one in Drosophila melanogaster (DTIS11). These proteins bind target mRNAs with AU-rich elements (AREs) via two C3H zinc finger domains and destabilize the mRNAs. We found that overexpression of mouse TIS11b or DTIS11 in the Drosophila retina dramatically reduced eye size, similar to the phenotype of eyes absent (eya) mutants. The eya transcript is one of many ARE-containing mRNAs in Drosophila. We showed that TIS11b reduced levels of eya mRNA in vivo. In addition, overexpression of Eya rescued the TIS11b overexpression phenotype. RNA pull-down and luciferase reporter analyses demonstrated that the DTIS11 RNA-binding domain is required for DTIS11 to bind the eya 3′ UTR and reduce levels of eya mRNA. Moreover, ectopic expression of DTIS11 in Drosophila S2 cells decreased levels of eya mRNA and reduced cell viability. Consistent with these results, TTP proteins overexpressed in MCF7 human breast cancer cells were associated with eya homologue 2 (EYA2) mRNA, and caused a decrease in EYA2 mRNA stability and cell viability. Our results suggest that eya mRNA is a target of TTP proteins, and that downregulation of EYA by TTP may lead to reduced cell viability in Drosophila and human cells.